Impact of Daily Consumption of Iron Fortified Ready-to-Eat Cereal and Pumpkin Seed Kernels (Cucurbita pepo L.) on Serum Iron in Adult Women - MR Naghii; M Mofid (Institue of Medicinal Plants, ACECR, 2009)
Background: The objective of this study was to consider the effectiveness of consumption of iron fortified ready-to-eat cereal and pumpkin seed kernels as two sources of dietary iron on status of iron nutrition and response of hematological characteristics of women at reproductive ages. Methods: Eight healthy female, single or non pregnant subjects, aged 20-37 y consumed 30 g of iron fortified ready-to-eat cereal (providing 7.1 mg iron/day) plus 30 g of pumpkin seed kernels (providing 4.0 mg iron/day) for four weeks. Blood samples collected on the day 20 of menstrual cycles before and after consumption and indices of iron status such as reticulocyte count, Hb, Ht, serum ferritin, iron, TIBC, transferrin and transferrin saturation percent were determined. Results: Better response for iron status was observed after consumption period. The statistical analysis showed a significant difference between the pre and post consumption phase for higher serum iron, higher transferrin saturation percent, and lower TIBC. All individuals had higher serum iron after consumption. A significant positive correlation between the differences in serum iron levels and differences in transferrin saturation percentages and a significant negative correlation between the differences in serum iron levels and differences in TIBC was found, as well. Conclusion: Iron deficiency anemia is the most common nutritional problems in the world affecting billions of people through the world and impairs growth and cognition. Fortified foods contribute to maintaining optimal nutritional status and minimizing the likelihood of iron insufficiencies and use of fortified ready-to-eat cereals is a common strategy. The results showed that adding another food source of iron such as pumpkin seed kernels improves the iron status. Additional and longer studies using these two food products are recommended to further determine the effect of iron fortification on iron nutrition and status among the target population, and mainly in young children, adolescents, women of reproductive ages and pregnant women.